2003
DOI: 10.1074/jbc.c200596200
|View full text |Cite
|
Sign up to set email alerts
|

Two Short Segments of Smad3 Are Important for Specific Interaction of Smad3 with c-Ski and SnoN

Abstract: Cytokines of the transforming growth factor-␤ (TGF-␤)1 superfamily bind to two different serine/threonine kinase receptors, type I and type II, and transmit intracellular signals through Smad proteins (1). Receptor-regulated Smads (RSmads) are directly phosphorylated by type I receptors, and form complexes with common-partner Smad (Co-Smad). The R-Smad⅐Co-Smad complexes translocate into the nucleus, where they regulate transcription of target genes through interacting with various transcription factors and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 31 publications
4
47
0
1
Order By: Relevance
“…This result is consistent with our previous observation that c-Ski interacts with Smad2/3 through the upper surface of the MH2 toroid structure of Smad2/3 trimer (Mizuide et al, 2003). We further examined how c-Ski affects Smad heteromeric complex using c-Ski ⌬S2/3, which interacts with Smad4 but not with R-Smads.…”
Section: Interaction With Smad4 Is Essential For Suppression Of Bmp Ssupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with our previous observation that c-Ski interacts with Smad2/3 through the upper surface of the MH2 toroid structure of Smad2/3 trimer (Mizuide et al, 2003). We further examined how c-Ski affects Smad heteromeric complex using c-Ski ⌬S2/3, which interacts with Smad4 but not with R-Smads.…”
Section: Interaction With Smad4 Is Essential For Suppression Of Bmp Ssupporting
confidence: 90%
“…In the model, c-Ski binds to L3 loop of Smad4, a loop that is responsible for interaction with R-Smads; thus, c-Ski inhibits formation of active Smad complex between R-Smads and Co-Smad. Although BMP-specific R-Smads bind to c-Ski only weakly (Akiyoshi et al, 1999;Mizuide et al, 2003), it has been shown that c-Ski inhibits BMP signaling in mammals and in Xenopus (Amaravadi et al, 1997;Wang et al, 2000).The ARPG mutant of Ski protein was first described in v-Ski as a transformation-defective mutant (Colmenares et al, 1991). The ARPG mutation is an insertional mutation of four amino acids (Ala-Arg-Pro-Gly), replacing Asp in a po- et al, 1991).…”
mentioning
confidence: 99%
“…The PPPPY motif sequence of RNF11 is identical to that of Smads 2, 3 and 7, which have been shown to bind WW domains of Smurf2 Ub ligase and mediate the ubiquitination and degradation of various target proteins (Coopman et al, 2000;Longnecker et al, 2000). Smurf2 plays a key role in the ubiquitination and proteasomal degradation of receptor-activated Smad2 and Smad3, and corepressor SnoN (Bonni et al, 2001;Mizuide et al, 2003). The Smurf2 and Smad7 complex ubiquitinates TbRI, a key event resulting in degradation of the receptor and TGFb resistance in cancer cells (Kavsak et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data strongly suggest that under these experimental conditions, two distinct domains in Ski can independently mediate interaction of Ski with Smad3. Interestingly, Mizuide et al (15) recently identified two separate sites in the MH2 domain of Smad2/3, which mediate interaction with Ski/ Sno. Thus, it is possible that two distinct interfaces of Ski/Sno and Smad2/3 facilitate interaction with each other.…”
Section: Ski Allows Smad3/4 Heteromer Formation 32490mentioning
confidence: 99%